Evaluation of gas explosion overpressures at configurations with irregularly arranged obstacles - Li, J.; Ma, G.; Abdel-Jawad, M.; Hao, Hong (American Society of Civil Engineers (ASCE), 2015)
Rapid analytical methods for the calculation of gas explosion overpressures in confined and congested regions are of great value where a benchmark value is sought rather than a time consuming detailed analysis obtainable by computational fluid dynamics (CFD). While earlier correlations have been compared directly to experiments, the geometries used were often simplistic and displayed homogeneity in confinement and congestion. Realistic geometries typically display a high degree of inhomogeneity in confinement and congestion. Here the authors examine geometries where the confinement and congestion were deliberately varied such that some of the geometries possessed inhomogeneity of both parameters. Little experimental data exists for such configurations and hence the authors examine these configurations using CFD. The CFD overpressure predictions at various target locations for 400 scenarios are compared with the results from a newly derived correlation and the correlation of the guidance for the application of the multi-energy method (GAME). It is found that the overpressure predictions obtained using the correlation still better agrees with the CFD modeling results compared with the GAME correlation suggesting. To show the importance of increased accuracy in these cases, a structural damage level evaluation process is used to place the damage levels for four monitor points on a p-i curve, and the results show that often these damage levels are near critical, demonstrating the need for improved accuracy.